Some bio-characteristics of Labyrinthula from the north coasts of Vietnam - Hung, Nguyen Dinh; Nam, Hoang Sy; Anh, Hoang Lan; Hong, Dang Diem (Academia Journal of Biology, 2014)
Labyrinthula is a heterotrophic microalgal genus with spindle - shape bodies and a gliding movement along ectoplasmic networks. The ectoplasmic network of Labyrinthula can digest bacteria, yeast and other organisms. They started to attract attention because of their ability to produce polyunsaturated fatty acids (PUFAs) such as docosahexaenoic acid (DHA, C22: 6n-3) and docosapentaenoic acid (DPA; C22: 5n-6) which are important for metabolism of human and animals. This microalgal genus is diverse in species compositions because of climate and water quality of Vietnam sea are suitable for them. 276 fallen-leaf samples are collected from five northern coasts of Vietnam: Quangninh, Haiphong, Thaibinh, Namdinh, Thanhhoa. 54 strains Labyrinthula spp. are isolated successfully. After screening based on optimal cultural conditions in solid medium, we have identified 10 strains among them having high growth rate, content of total lipid and producing high amount of PUFAs such as QN5, QN37, QN42, QN48; HP43; ND21, ND23, ND31, ND32, ND50. 10 above - mentioned strains have been used with purpose to obtain biomass for further investgations.